Wearable technology for occupational risk assessment: potential avenues for applications - Pavón, Ignacio (2018)
This paper analyzes the opportunities offered by wearable technology for occupational risk assessment. A wide range of electronic devices known as “wearables” include sensors that provide interesting features with the potential to be used in workers’ monitoring, sending alert signs (e.g., visual, sound, haptic) and training. In this paper, it has been identified the primary applications in which wearables are being used for risk assessment (motion and activity detection, recognition of work-related musculoskeletal disorders, fall detection, evaluation of exposure to different physical agents, evaluation of exposure to chemical agents, and location of potential hazards). Also, it has been identified the opportunities for improvement in the future using the potential of emerging technologies.